Down-Regulation of AKT Signalling by Ursolic Acid Induces Intrinsic Apoptosis and Sensitization to Doxorubicin in Soft Tissue Sarcoma. - Victor Hugo Villar; Oliver Vögler; Francisca Barceló; Javier Martín-Broto; Jordi Martínez-Serra; Valentina Ruiz-Gutiérrez; Regina Alemany (PLoS ONE, 2016)
Several important biological activities have been attributed to the pentacyclic triterpene ursolic acid (UA), being its antitumoral effect extensively studied in human adenocarcinomas. In this work, we focused on the efficacy and molecular mechanisms involved in the antitumoral effects of UA, as single agent or combined with doxorubicin (DXR), in human soft tissue sarcoma cells. UA (5-50 μM) strongly inhibited (up to 80%) the viability of STS cells at 24 h and its proliferation in soft agar, with higher concentrations increasing apoptotic death up to 30%. UA treatment (6-9 h) strongly blocked the survival AKT/GSK3β/β-catenin signalling pathway, which led to a concomitant reduction of the anti-apoptotic proteins c-Myc and p21, altogether resulting in the activation of intrinsic apoptosis. Interestingly, UA at low concentrations (10-15 μM) enhanced the antitumoral effects of DXR by up to 2-fold, while in parallel inhibiting DXR-induced AKT activation and p21 expression, two proteins implicated in antitumoral drug resistance and cell survival. In conclusion, UA is able to induce intrinsic apoptosis in human STS cells and also to sensitize these cells to DXR by blocking the AKT signalling pathway. Therefore, UA may have beneficial effects, if used as nutraceutical adjuvant during standard chemotherapy treatment of STS.